Physical, chemical, and biological analysis of drinking water quality in Tulungagung regency, East Java - Indra Lasmana Tarigan (Department of D3 Medical Technology Laboratory STIKes Hutama Abdi Husada Tulungagung, 2020)
This study aims to analyze the quality of water in Tulungagung. Identification carried out is a physical test including pH, salinity, color, and temperature. As well as chemical tests, including alkalinity test, CO2 content, Cl, and Water Hardness. The sample water collected from six locations in Tulungagung Regency which are Sendang, Rejotangan, Campurdarat, Keras, Ngunut, and Tanggunggunung. From the pH test was obtained that all the sample water qualifies as good water (pH 6.5 to 8.0). The content of CO2 water samples shows that result with the highest CO2 21 ppm and the lowest 18ppm. Whereas the Cl test obtained the highest 135.3 ppm and the lowest was 52.7 ppm This analysis data was enriched with hardness test results with the highest hardness 60.9 D while the lowest hardness water was 20.9 D